Optimization of electric field uniformity of multi-needle electrospinning nozzle - Zhu, Ziming (2020)
Multi-needle electrospinning technology is a method for mass production of nanofibers, which can improve the production efficiency of nanofibers by increasing the number and density of needles for multi-needle electrospinning. However, when the arrangement density of the needle is high, the electric field of the needle tip is not uniform, causing instability such as jet dripping and broken jet. In this paper, the electric field uniformity optimization problem of multi-needle electrospinning technology is used to simulate the needle tip electric field by using COMSOL finite element analysis software. The influence of the needle size and the dielectric material on the electric field of the tip was studied. Finally, the method of using dielectric material on the tip of the middle part of the needle is beneficial to the electric field uniformity. The uniformity of the needle tip electric field in the case of high-density arrangement of the needle is realized, and the nozzle is provided for mass production of nanofibers by multi-needle electrospinning.